Experience of the usage intraoperative radiation therapy in patients with early breast cancer - A. G. Manikhas; L. A. Gor; E. E. Topuzov; A. S. Oganesyan; O. I. Fedorova; I. V. Kalinin (Опухоли женской репродуктивной системы, 2022)
Background. Comprehensive treatment of breast cancer includes surgery, radiation therapy and systemic treatment. Radiation therapy plays an integral role in the treatment of early breast cancer. The appointment of a targeted dose of radiation to the bed of the primary tumor reduces the risk of local recurrence.Objective: to evaluate the effectiveness of intraoperative radiation therapy in the treatment of early breast cancer.Materials and methods. A retrospective study was conducted on the basis of the St. Petersburg City Clinical Oncology Center. Patients with organ-preserving surgery and intraoperative radiation therapy were selected. Of the 352 patients, 273 patients met the inclusion/non-inclusion criteria. Inclusion criteria were verified breast cancer, clinical stage I–IIA, tumor size no more than 3 cm, absence of visible axillary lymph nodes and monocentric nature of tumor growth. All patients underwent sectoral resection of the mammary gland with a biopsy of the sentinel lymph nodes and intraoperative radiation therapy.Results. The mean age of the patients was 59 years. For 273 patients, the median follow-up was 59.1 months. During this period, 18 (6.6 %) local recurrences of the disease were noted, of which 7 (39 %) patients with luminal A, 6 (33 %) patients with luminal B, 1 (6 %) patient with luminal B HER2/neu 3+, and 4 (22 %) patients with triple negative breast cancer. Within 3 years of follow-up, recurrence-free survival was 98.5 %, within 5 years – 96.4 %.Conclusion. The use of intraoperative radiation therapy for early breast cancer is an effective and safe treatment method.